Efektifitas Penerapan Sertifikat HKI sebagai Jaminan Kredit bagi Pelaku Ekonomi Kreatif dan UMKM - Faisal Herisetiawan; Patma Sari (Syntax Idea)
In improving the economy in Indonesia, the government is very aggressive in supporting the development of the creative economy, especially SMEs, one of which is by providing financing facilities with guaranteed intellectual property rights certificates. The problem that has occurred to date is that guarantee facilities using intellectual property rights certificates are very rarely implemented, there are many influencing factors such as , banks that apply the precautionary principle and few people use intellectual property rights registration facilities due to lack of information. This research aims to examine the effectiveness of implementing intellectual property rights certificates as collateral for credit financing for creative economy actors and MSMEs. The type of research used in writing is a normative legal research method which emphasizes secondary data. In determining whether a regulation is effective or not in its implementation there are at least five determining factors, namely, legal factors, law enforcement factors, facilities and facilities factors, community factors and cultural factors. The effectiveness of implementing intellectual property rights certificates as debt collateral in Indonesia is still not running well in accordance with what was expected by lawmakers. Regulations regarding intellectual property rights as debt collateral have been around for a long time but in practice it is very difficult to implement.